A new RNS based DA approach for inner product computation - Vun, Chan Hua (2013)
This paper presents a novel method to perform inner product computation based on the distributed arithmetic principles. The input data are represented in the residue domain and are encoded using the thermometer code format while the output data are encoded in the one-hot code format. Compared to the conventional distributed arithmetic based system using binary coded format to represent the residues, the proposed system using the thermometer code encoded residues provides a simple means to perform the modular inner products computation due to the absence of the 2 modulo operation encountered in conventional binary code encoded system. In addition, the modulo adder used in the proposed system can be implemented using simple shifter based circuit utilizing one-hot code format. As there is no carry propagation involved in the addition using one-hot code, while the modulo operation can be performed automatically during the addition process, the operating speed of the one-hot code based modulo adder is much superior compared to the conventional binary code based modulo adder. As inner product is used extensively in FIR filter design, SPICE simulation results for an FIR filter implemented using the proposed system is also presented to demonstrate the validity of the proposed scheme.